2003
DOI: 10.1063/1.1596392
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of the conversion of gas phase methanediol to formaldehyde

Abstract: Methanediol, or methylene glycol, is a product of the liquid phase reaction of water and formaldehyde and is a predicted interstellar grain surface species. Detection of this molecule in a hot core environment would advance the understanding of complex organic chemistry in the interstellar medium, but its laboratory spectroscopic characterization is a prerequisite for such observational searches. This theoretical study investigates the unimolecular decomposition of methanediol, specifically the thermodynamic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 16 publications
7
65
0
Order By: Relevance
“…One interesting case of intramolecular hydrogen bonding is that of geminal diols due to the increased strain imposed by the two alcohol groups on a single carbon. The gem diol is well-known in aqueous solution through NMR investigations [10,11,17], however to the best of our knowledge, it has not been observed in the gas-phase in any system. The gem diol forms intermolecular hydrogen bonds consequently lowering the vapor pressure compared to the carbonyl analogues.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…One interesting case of intramolecular hydrogen bonding is that of geminal diols due to the increased strain imposed by the two alcohol groups on a single carbon. The gem diol is well-known in aqueous solution through NMR investigations [10,11,17], however to the best of our knowledge, it has not been observed in the gas-phase in any system. The gem diol forms intermolecular hydrogen bonds consequently lowering the vapor pressure compared to the carbonyl analogues.…”
Section: Introductionmentioning
confidence: 92%
“…These compounds are found in the highly oxidized material of secondary organic aerosols (SOA) [1][2][3][4][5][6][7][8][9]. Aldehydes, and to a lesser extent ketones, are known to form a gem diol in the presence of water [10,11]. The gem diol drastically changes the physical and chemical properties of the molecules, which impacts the partitioning between gas and particle phase as well as the chemistry of such molecules in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…88,89 For instance, in excess water GAM ͑ϳ93%͒ is heavily favored compared to GA. 75 The formation of GAM, the hydrated geminal diol form of GA, occurs through a water mediated equilibrium and has a much lower vapor pressure than GA. 82 Most work on gem diols has been confined to theory or solution phase experiments, due to their low vapor pressure. [88][89][90][91][92][93] The lowest energy conformer of GAM has an intramolecular hydrogen bond from one of the alcohol groups ͑OH Hb ͒ to the carbonyl oxygen of the acid group. The two other OH groups ͑we designate the free alcohol as OH Fr and the acid OH as OH Ac ͒ are capable of forming intermolecular hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…If such was the case, we would expect to see a dominant population of the hydrated form during gas phase studies of this compound, which is not observed experimentally. 7,45 More recently, Kent et al 46 have conducted a theoretical study of the conversion of gas phase methandiol to formaldehyde. Using the HF, MP2, MP4, CCSD, CCSD(T), and QCI(T) model chemistries with the cc-pVDZ and cc-pVTZ basis sets, these authors obtained Δ hydr G°( g) ranging from 1.0 to 3.3 kcal/mol, with the highest level CCSD(T)/cc-pVTZ and QCI(T)/cc-pVTZ methods yielding Δ hydr G°( g) of 1.0 and 1.1 kcal/mol, respectively.…”
Section: Resultsmentioning
confidence: 99%